2019
DOI: 10.2147/ott.s192377
|View full text |Cite|
|
Sign up to set email alerts
|

<p>The inhibitive effect of sh-HIF1A-AS2 on the proliferation, invasion, and pathological damage of breast cancer via targeting miR-548c-3p through regulating HIF-1&alpha;/VEGF pathway in vitro and vivo</p>

Abstract: BackgroundBreast cancer (BC) has been the commonest malignant tumor with a low survival rate among woman. Long non-coding RNA hypoxia-inducible factor-1 alpha antisense RNA-2 (HIF1A-AS2) was correlated with various cancers.PurposeThe study aimed to investigate the roles and related underlying molecular mechanisms of HIF1A-AS2 in BC.Material and methodsTarget relationships were speculated by Targetscan 7.0 and confirmed by dual luciferase reporter assay. Proteins levels were monitored by RT-qPCR, Western blot a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…21 HIF1A-AS2 was also found to sponge several miRNAs, such as miR-129-5p, miR-548c-3p and miR-665. 12,22,23 In our study, we demonstrated that HIF1A-AS2 interacted with miR-153-5p. We showed that miR-153-5p expression was upregulated after HIF1A-AS2 knockdown, and HIF1A-AS2 level was negatively correlated with miR-153-5p expression in NSCLC tissues.…”
Section: Dovepresssupporting
confidence: 56%
“…21 HIF1A-AS2 was also found to sponge several miRNAs, such as miR-129-5p, miR-548c-3p and miR-665. 12,22,23 In our study, we demonstrated that HIF1A-AS2 interacted with miR-153-5p. We showed that miR-153-5p expression was upregulated after HIF1A-AS2 knockdown, and HIF1A-AS2 level was negatively correlated with miR-153-5p expression in NSCLC tissues.…”
Section: Dovepresssupporting
confidence: 56%
“…A few studies have discussed this hypothesis, such as in non-small cell lung cancer [ 135 ] and ovarian cancer [ 136 ], but it has not been validated experimentally. Despite that, HIF1A-AS2 can promote HIF1A expression and regulate the HIF1A/VEGFA pathway by sponging miR-548c-3p, exerting a proangiogenic function in breast cancer [ 137 ]. In bladder cancer samples following treatment with cisplatin (a chemotherapy drug), HIF1A-AS2 and HIF1A are both overexpressed and correlate positively [ 138 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also found that miR-548c-3p was a downstream target of hsa_circ_0101145. Previous studies have indicated that miR-548c-3p expression can inhibit the progression of many cancers, including papillary thyroid carcinoma [20], breast cancer [21], and osteosarcoma [22]. We found that miR-548c-3p expression decreased in HCC tissues.…”
Section: Agingmentioning
confidence: 51%